Penerapan Metode Brainstroming dalam Pembelajaran PPKN Kelas 6 SD Untuk Menanggulangi Kejenuhan Siswa Di Kelas - Akbar Nugraha Siagian; Nur Hayati Hasibuan; Nur Hidayah Siregar; Santa Situmorang (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
The Brainstorming Learning Model is the right model for the type of student who is active but still lacks confidence in expressing opinions or ideas. The Brainstorming Learning Model motivates students to share the ideas they have without any pressure. The purpose of using the Brainstorming learning model is to find out whether there is a significant positive impact on the Brainstorming learning model on student boredom during the learning process of students in class VI Civics at Elementary School. This research method uses qualitative research methods. The research results show that the Brainstorming learning model has an effect on eliminating students' boredom in the learning process. This can cause students to feel involved and their ideas are valued, which in turn motivates them to learn with more interest.